The Wizard of Ooze - Stine, R L (New York Scholastic Inc, 2010)
When Marco finds a rare edition of the Ooze comic book at HorrorLand, he finds that many monstrous collectors would do anything to get their hands on the comic
Horror & Ghost Stories
Keywords: Amusement parks -- Juvenile fiction; Games -- Juvenile fiction; Monsters -- Juvenile fiction